Jewishness in the novels of Saul Bellow and Bernard Malamud - Salátová, Miroslava (Univerzita Pardubice, 2009)
The work concerns Jewishness and its perception by American Jewish immigrants in the works by Saul Bellow Mr. Sammler' planet and Bernard Malamud The Assistant. Jewishness is in the work reflected in suffering connected mainly with death and the Holocaust, in family system as well as in the question religion.
Židovství v románech Saula Bellowa a Bernarda Malamuda
Keywords: židovství; holokaust; menšiny; Judaism; Minority; holocaust